2007
DOI: 10.1002/ptr.2085
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Hypericum perforatum blocks caffeine‐induced locomotor activity in mice: a possible role of nitric oxide

Abstract: The present study investigated the effects of HPE on caffeine-induced locomotor activity in mice. Caffeine (4 -16 mg/kg) or saline were given to adult male Swiss-Webster mice, and the locomotor activity was immediately measured for 30 min. HPE (6-48 mg/kg) and saline were injected to another group of mice and the locomotor activity was measured 20 min later. HPE (6-24 mg/kg) was also administered to another group of mice 20 min before caffeine (16 mg/kg) injections and the locomotor activity was recorded for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…The lack of effect of l -arginine and sildenafil on the tolerance to FNZ is difficult to explain. Some studies have shown that l -arginine up to 1000 mg/kg was effective without impairing open-field locomotor activity in mice (Ulusu et al 2005; Uzbay et al 2007). Therefore, it is possible that too low, inefficient doses of the NO precursor (up to 250 mg/kg) would account for the lack of effect of l -arginine on the tolerance to FNZ in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of effect of l -arginine and sildenafil on the tolerance to FNZ is difficult to explain. Some studies have shown that l -arginine up to 1000 mg/kg was effective without impairing open-field locomotor activity in mice (Ulusu et al 2005; Uzbay et al 2007). Therefore, it is possible that too low, inefficient doses of the NO precursor (up to 250 mg/kg) would account for the lack of effect of l -arginine on the tolerance to FNZ in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
“…HP possesses potent antioxidant and anti‐inflammatory properties due to the presence of several bioactive compounds including naphthodianthrones (hypericin, pseudohypericin, protohypericin, protopseudohypericin, and cyclopseudohypericin), flavonoids (quercetin, rutin, and luteolin), hyperforin and tannins . It is used in folk medicine against diabetes mellitus (DM) . Many researchers have demonstrated the blood glucose lowering effect of HP; recent studies point out the potential therapeutic uses of HP regardless of hypoglycemic effect .…”
Section: Introductionmentioning
confidence: 99%
“…The hyperforin-induced cascade involving CREB and BDNF is controlled by Ca 2 + ions and occurs specifically in the cortex but not in the hippoistered alone. The inhibitory effect of SJW on caffeineinduced locomotor activity may therefore be related to an inhibition of the enzyme NO-synthetase [31].…”
Section: Effect On Ion Channelsmentioning
confidence: 99%